ANALISIS RISK BASED CAPITAL (RBC), RETURN ON ASSET (ROA) DAN RETURN ON EQUITY ROE) TERHADAP KINERJA KEUANGANPT PRUDENTIAL LIFE ASSURANCE TAHUN 2012-2021 - siti nurcahayati; Chofifah Febrianti (JURNAL KONSISTEN, 2024)
Purpose. This study is to determine and analyze how Risk Based Capital (RBC) Return on Asset (ROA) and Return on Equity (ROE) affect Financial Performance at PT Prudential Life Assurance in 2012-2021. Methods. The approach used in this study is a quantitative descriptive approach, namely the data obtained is processed in such a way as to provide systematic, factual and accurate data regarding the problems studied. Results. The RBC generated from the average calculation of 756.30% can be categorized as very good. The ROA generated from the average calculation of 6.96% can be categorized as a company that has a poor ROA because the company is unable to use the total assets owned by the company effectively and efficiently in generating profits, the ROE generated from the average calculation of 67.87% can be categorized as very good, this shows the company's ability to manage its equity in generating profits quite well Implications. Based on the research results, it shows that Risk Based Capital, Return on Assets and Return on Equity at PT Prudential Life Assurance in 2012-2021 experienced. Keywords. Risk Based Capital; Return on Asset; Return on Equity